Effect of Adding Online Social Support Tools to an Adult Walking Program: A Pilot Randomized Controlled Trial. Issue 1 (January 2017) - Monroe, Courtney M.; Bassett, David R.; Fitzhugh, Eugene C.; Raynor, Hollie A.; Thompson, Dixie L.
This pilot study examined the efficacy of providing access to online social support tools on adults' step counts during a technology-mediated walking intervention. Sixty-three insufficiently active adults were randomized to a 12-week walking intervention with (SUPPORT) or without (NO SUPPORT) access to online social support tools. Both groups received a pedometer, step goals, and access to relevant websites. The SUPPORT group also received access to online social support tools. A mixed-factor analysis of variance was conducted to examine within- and between-group differences in measures of daily steps, psychosocial indicators, and health. Both groups significantly (p < .05) increased their daily steps over time from baseline by 1, 401 (SUPPORT) and 2, 461 (NO SUPPORT), with no significant differences between groups. Psychosocial and health improvements were no greater for SUPPORT versus NO SUPPORT. The SUPPORT group's use of the online social support tools was low. Results suggest that giving adults access to online social support tools during a technology-mediated walking program did not lead to an enhanced increase in daily steps versus an identical program without these tools; however, the low use of these tools may have weakened their effect. Future studies should examine SUPPORT versus NO SUPPORT among groups with preexisting social ties.